Biology of black bass Micropterus salmoides (LacepÃ¨de, 1802) fifty years after the introduction in a small drainage of the Upper ParanÃ¡ River basin, Brazil - DIEGO AZEVEDO ZOCCAL GARCIA; ALEXANDRO DERLY AUGUSTO COSTA; GEAN LUCAS ALVES LEME; MÃRIO LUÃS ORSI (Society for Indonesian Biodiversity, 2014)
Garcia DAZ, Costa ADA, Leme GLA, Orsi ML. 2014. Biology of black bass Micropterus salmoides (LacepÃ¨de, 1802) fifty years after the introduction in a small drainage of the Upper ParanÃ¡ River basin, Brazil. Biodiversitas 15: 180-185. The dispersion of organisms byhuman actions has been the major source of changes in the natural distribution of species, making the introduction of non-native speciesa threat to biological diversity. Micropterus salmoides is a fish originating from North America, which was introduced in a lagoon in theEcological Park of Fazenda Monte Alegre in southern Brazil over 50 years ago. The reproductive activity, weight-length relationshipand relative condition factor were analyzed to evaluate the health parameters of the species. The result allows us to classify thereproductive activity of this population as moderate. It was found that the health condition patterns are identical to those theoreticallyexpected. The occurrence of individuals downstream of the lagoon shows that the population has been presenting dispersion conditionsto new environments, posing a threat to local biodiversity. Management measures, such as isolation or eradication of the population, arerequired to control the species within the studied site, and prevent its dispersion into natural watercourses.